Performance investigation of a new carbon–silver microspheres/epoxy resin superhydrophobic coating. (2nd June 2020) - Zhao, Meiyun; Tian, Sen; Zhao, Xinze; Wu, Yang; Tan, Mingyi; Xing, Jing Tang
ABSTRACT: Based on the reaction of AgNO3 and dopamine-hydrochloride in the weak alkaline conditions, carbon–silver microspheres with layered structure were produced, which subsequently were surface-modified with 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane to produce a superhydrophobic carbon–silver powder. By using the advantage of high viscosity epoxy resin, this powder can be used to various nonmetal substrates to form robust superhydrophobic coatings. The hydrophobicity, surface morphology, chemical composition, mechanical stability, chemical durability, self-cleaning, antifouling and thermal stability are studied by means of the contact angle metre, scanning electron microscope, X-ray photoelectron spectroscope measurements, three-dimensional topography metre and thermal gravimetric analyses. The results indicate that the prepared powder can be applied to most nonmetal substrates to form excellent superhydrophobic coatings with very good comprehensive performance.